Diagnosing the Problem of Anti-Politicians: A Review and an Agenda. (November 2016) - Corbett, Jack
In response to growing popular dissatisfaction with politics and politicians, several scholars have sought to explain the cause of this malaise and demonstrate what can be done about it. To tease out the signiﬁcance of four recent additions to this discussion, this article reviews how they diagnose the problem of anti-politicians and what they consider the cure might be. Riddell and Flinders, it is argued, view the problem in terms of an expectations 'gap', while Kane and Patapan, and Medvic cast it as a leadership 'paradox' or an expectations 'trap'. The former two primarily see greater citizen participation, generated via institutional reform or revived civic values, as the solution, whereas the latter two question whether the problem can or should be solved at all. The article concludes that while these books provide important insights, by and large they neglect to take serious or systematic account of the views, experiences and reﬂections of political leaders themselves. To take this research agenda forward, this omission warrants further attention. Flinders, M. (2012) Defending Politics: Why Democracy Matters in the Twenty-First Century . Oxford: Oxford University Press. Kane, J. and Patapan, H. (2012) The Democratic Leader: How Democracy Deﬁnes, Empowers and Limits its Leaders . Oxford: Oxford University Press. Medvic, S. (2013) In Defense of Politicians. The Expectations Trap and Its Threat to Democracy . New York: Routledge. Riddell, P. (2011) In Defence of Politicians (In spite of Themselves) . London: Biteback.